Synthesis of a surface mounted metal–organic framework on gold using a Au–carbene self-assembled monolayer linkage. (19th February 2019) - Frederick, Esther; Shaw, Travis W.; Frith, Matthew G.; Bernasek, Steven L.
Abstract : Carbene based self-assembled monolayers are demonstrated to be effective supports for forming highly stable surface-mounted metal–organic frameworks on gold substrates. Abstract : Applications using metal–organic frameworks (MOFs) in devices require a degree of positional control that necessitates an attachment more robust than direct MOF growth on a bare substrate. To date, the precise positioning of MOFs on Au surfaces has been accomplished using thiol–Au linkages, which lack the long-term stability needed for device applications. This study utilized a Au–carbene monolayer with long term stability developed by Crudden et al. as the linkage between a gold substrate and MOF. The Au–carbene surface mounted MOF (surMOF) was successfully synthesized using layer by layer deposition and characterized using XRD, XPS, and AFM.